Evaluation of Liquefaction Potential of Coastal Alluvium Using SPT Data - A Comparative Case Study. Issue 1 (November 2020) - Muduli, P K; Karna, P; Samal, M R
Abstract: Earthquake induced soil liquefaction causes large scale damage to the infrastructures, lifeline systems and harbor facilities. Evaluation of the liquefaction potential of a soil subjected to seismic loading is one of the most important steps towards mitigation of liquefaction-induced damages. Nowadays, evaluation of liquefaction potential in case of susceptible soils is considered as a routine practice. The proposed coastal National Highway (NH) connecting Digha of West Bengal to Gopalpur of Odisha under Bharatmala Pariyojana is a major NH project undertaken by the National Highway Authority of India (NHAI). The district Kendrapara lies in 20° 20' N to 20° 37' N Latitude and 86° 14' E to 87° 01' E Longitude and situated in central coastal plain on the Bay of Bengal and comes under the seismic zone III as per the seismic zoning map of Bureau of Indian Standards (IS 1893 (Part 1): 2016). As the coastal alluvium is susceptible to liquefaction, some of the SPT bore log data collected from the two coastal locations of Kendrapara district of Odisha under the above project is used for evaluation of liquefaction potential of soil following available statistical method, artificial neural network (ANN) based method and multi-gene genetic programming (MGGP) based method. It is observed that some layers of the above soil are liquefiable considering a future seismic event of moment magnitude (Mw), 7. All the above three methods are predicting well the liquefaction and non-liquefaction cases.